Needle Arthroscopy for Osteochondral Lesions of the First Metatarsophalangeal Joint: A Standardized Approach - Alex B. Walinga, M.D.; Jari Dahmen, M.D., B.Sc.; Tobias Stornebrink, M.D.; Gino M.M.J. Kerkhoffs, M.D., Ph.D. (Arthroscopy Techniques, 2023)
Cartilage and osteochondral lesions of the first metatarsophalangeal (MTP-1) joint are characterized by pain during weight bearing and walking. The lesions often require surgical intervention(s). Arthroscopic bone marrow stimulation may be considered the preferred operative intervention for small lesions. Technological advances, patient preferences, and economic considerations combine to foster the development of minimally invasive needle arthroscopic procedures. This technical note presents and highlights our minimally invasive surgical technique for needle arthroscopic treatment through bone marrow stimulation for osteochondral lesions of the MTP-1 joint.